2022
DOI: 10.3390/genes13091607
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantitation of Novel ABI3 Isoforms Relative to Alzheimer’s Disease Genetics and Neuropathology

Abstract: Elucidating the actions of genetic polymorphisms associated with the risk of Alzheimer’s disease (AD) may provide novel insights into underlying mechanisms. Two polymorphisms have implicated ABI3 as a modulator of AD risk. Here, we sought to identify ABI3 isoforms expressed in human AD and non-AD brain, quantify the more abundant isoforms as a function of AD genetics and neuropathology, and provide an initial in vitro characterization of the proteins produced by these novel isoforms. We report that ABI3 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The cDNA copy numbers for each sample were determined by quantitative polymerase chain reaction (qPCR) relative to standard curves that were amplified in parallel and were based upon previously purified and quantified PCR products, as described previously [ 27 , 31 , 32 , 33 ]. INPP5D isoforms were identified using ENSEMBL (version GRCh38:CM000664.2) and are referred to with ENSEMBL nomenclature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cDNA copy numbers for each sample were determined by quantitative polymerase chain reaction (qPCR) relative to standard curves that were amplified in parallel and were based upon previously purified and quantified PCR products, as described previously [ 27 , 31 , 32 , 33 ]. INPP5D isoforms were identified using ENSEMBL (version GRCh38:CM000664.2) and are referred to with ENSEMBL nomenclature.…”
Section: Methodsmentioning
confidence: 99%
“…Cell suspensions were centrifuged at 300× g for 5 min, and RNA was extracted from cell pellets using RNeasy kits according to the manufacturer’s instructions (Life Technologies, Carlsbad, CA USA). RNA was converted to cDNA by using random hexamers and SuperScript IV (Thermo, Waltham, MA USA) and subjected to PCR as described previously for human brain cDNA [ 27 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…ABI3 was also recently proposed as an early biomarker for AD 148 . Overall, a series of these studies have strongly implicated ABI3 in AD pathogenesis, likely through its involvement in microglial motility and/or phagocytosis, in relation to microglial migration into amyloid plaques 149 , 150 . Whether ABI3 is also involved in other neurodegenerative disorders remains to be determined.…”
Section: The Association Of Wrc Dysfunction With Brain Disordersmentioning
confidence: 99%
“…Recent human genetics studies of AD identified a risk variant in the Abelson interactor family member 3 ( ABI3 ) locus in late-onset AD (LOAD) patients ( 2 , 15 17 ). ABI3 is a microglia-enriched gene ( 16 , 18 , 19 ). It participates in the WASP-family verprolin homologous protein (WAVE) regulatory complex, which is involved in actin cytoskeleton organization ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%